The Potential to Use Smartphone‑based GNSS Receivers for Surveying - Gabryszuk, Justyna (Geomatics and Environmental Engineering, 2020)
The aim of the present study was to investigate the possibility of using smartphone‑grade GNSS receivers for surveying purposes and to examine their accuracy in terms of positioning. The paper presents an analysis of the results of test measurements made using two smartphones: a Huawei P8 lite, powered by Android 6.0 and an iPhone 6s, operating on IOS 10.1.1. Both devices were equipped with GPS and GLONASS modules and had the supporting system, A-GPS. Measurements were made on two test parcels of different shapes and sizes. The test procedure encompassed three measurement series (I-III), each of which consisted of five determinations. The determinations were done at 5-min time intervals and each new measuring session began after 90 min from the previous one. Measurements with the Huawei P8 lite were taken using the Locus Map app, and measurements with the iPhone 6s were performed with the use of Map‑o‑meter. The study consisted of determining the positioning accuracy of the test smartphones by comparing the results with reference coordinates obtained from RTN measurements using the Topcon HiPer V receiver with Magnet Tools software. Determinations of the reference coordinates were done with the help of the TPI NetPro network real‑time service corrections.